(untitled) (Global Journal of Science Frontier Research, 2021)
The knowledge of the dyeing species of the Patagonian steppe and the incessant development of the dyeing textile artisanal activity, motivated us to investigate the dyeing potential on merino wool of the ruderal plants of the city. While they are disposable in public spaces and undesirable in private parks and gardens, they are an unlimited material resource for natural dyes. Material was collected from urban and periurban areas. Using the mother recipe, the dye was obtained and three etching treatments were developed. Hue, luminosity and saturation were studied. 19 species were processed, obtaining the colors with the highest saturation in the post-etching process. The outstanding species are Chenopodium album L. and Dysphania ambrosioides (L.) Mosyakin & Clemants of the Chenopodiaceae family. Of the species studied, part of them have never been registered in the bibliography in use for this purpose. We consider knowledge of this resource of great value to enhance its use and preserve the native Patagonian floristic diversity.